MISTIK KRISTIANI - Adinuhgra, Silvester (SEPAKAT-Jurnal Pastoral Kateketik, 2017)
Abstract:We often understand about mystical life erroneously. It is sometimes think thatthe mystical phenomenon is a misconduct that originates in a pagan worldthat poison the source of pure water derived from Scripture. When we hear theword âMysticâ, we think that mystic is something high or a special charismathat is only given to certain people. But actually, the mystical experience isgiven to all the Christians. All Christians call to come into mystical life by ablessing of baptism. Mystic life is the deepest longing of a soul.